3D City Modelling with Oblique Photogrammetry Method. (2015) - Yalcin, Guler; Selcuk, Osman
Abstract: The urbanization is increasing exponentially all over the world. Technology-based devices and services such as Geographic Information Systems (GIS), remote sensing, vehicle navigation systems and internet map services have been observed in a rapid growth of urbanization. The ability to extend two-dimensional analytical functionality into the third dimension is one of the most significant developments in GIS technology. Modelling objects in 3D (three-dimension) has been very useful for some urban applications such as planning, management, representation of the urban sceneries etc. Nowadays, 3D city models play a more and more important role in GIS. Also 3D city modelling is one of the most growing research topics in the technology of photogrammetry. This paper presents first and initial studies in Turkey of creating 3D city model from aerial images using oblique photogrammetry method. For this project, a 3D city model of Konya city in Turkey, is prepared in three level of detail (LoD). The fourth, also the last, level (LoD4) is used to texture interior of the buildings for only 5 historical, touristic and religious buildings: Mevlana Museum, Selimiye Mosque, Şerafettin Mosque, Aziziye Mosque, İnce Minareli Madrasa (Museum). This is also the first application example on 3D city modelling by using oblique photogrammetry in Turkey.